Implementasi Manajemen Mutu dalam Meningkatkan Kinerja Guru - Lufafi, Muhammad Hamid; Makruf, Imam (El-Idare, 2024)
This research aims to explore the implementation of Integrated Quality Management (IQM) in improving teacher performance at MTs Al-Furqon Sanden. Through a qualitative approach with a case study design, data were obtained through interviews, observations, and document studies. The results indicate that mature strategic planning has been conducted, with the development of madrasah work plans covering various activity programs. Organization and personnel management are carried out through the formation of a team implementing teacher performance improvement management. The implementation of programs and activities, including teacher mentoring and motivational seminars, has been carried out regularly. Identification of internal and external issues has also been conducted, with appropriate issue-handling strategies. Teacher involvement in decision-making processes and the implementation of performance improvement programs are also strengthened. Transparency and accountability are key principles in evaluating and reporting teacher performance. Thus, the implementation of IQM at MTs Al-Furqon Sanden has brought about positive changes in improving teacher performance and overall educational quality. This research provides valuable insights for the development of more effective educational management strategies.